Leather-based samarium boride composite material as well as preparation method and application thereof
The preparation of leather-based samarium boride composite material has solved the problems of high density and poor flexibility of traditional neutron shielding materials, achieving lightweight and efficient neutron protection, and promoting the green and multifunctional development of nuclear protection materials.
Patent Information
- Application Number
- CN202510556415.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-11-11
AI Technical Summary
Traditional neutron shielding materials are characterized by high density, poor flexibility, and insufficient environmental friendliness, making it difficult to meet the needs of wearable protective equipment and lightweight nuclear facilities. The application of leather-based materials in neutron shielding has not been fully explored.
By combining a leather matrix with the neutron-absorbing component samarium boride, a leather-based samarium boride composite material is constructed. The three-dimensional fiber network structure of leather is used to load samarium boride, thereby achieving neutron absorption functionalization. Vacuum drying technology is combined to ensure the uniformity of the composite.
The prepared leather-based samarium boride composite material exhibits high-efficiency neutron shielding performance in the field of neutron protection, while also being lightweight and flexible. This expands the high-value-added applications of leather materials and promotes the green and multifunctional development of nuclear protection materials.
Smart Images

Figure CN120924742A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of shielding materials technology, and in particular to a leather-based samarium boride composite material, its preparation method, and its application. Background Technology
[0002] With the rapid development of nuclear energy technology, the research on neutron radiation protection materials has become an important topic in the field of nuclear safety. Neutrons, as uncharged high-energy particles, possess extremely strong penetrating power. When they interact with matter, they not only cause severe radiation damage to human tissues but also trigger secondary radiation (such as gamma rays), further increasing the difficulty of protection. Traditional neutron shielding materials (such as boron-containing polyethylene, concrete, and heavy metal composites) are widely used in industrial settings, but they generally suffer from high density, poor flexibility, and insufficient environmental friendliness, making it difficult to meet the needs of special scenarios (such as wearable protective equipment and lightweight nuclear facilities). Therefore, developing novel neutron protection materials that combine high-efficiency shielding performance, lightweight design, flexibility, and sustainability has become a key research direction in radiation protection materials.
[0003] In recent years, biomass-based composite materials have attracted much attention due to their renewability, low environmental impact, and ability to be functionalized. Leather, as a natural collagen fiber-based porous material, possesses a unique hierarchical structure, excellent mechanical properties, and processability, demonstrating great potential in the field of functional materials. Its three-dimensional fibrous network structure provides an ideal carrier for loading functional components (such as neutron-absorbing elements and nanoparticles), while the inherent chemically active sites of collagen fibers facilitate functional enhancement through chemical modification or physical composites. However, current research on leather-based materials mainly focuses on mechanical reinforcement or electromagnetic shielding, and its application in radiation protection, especially neutron shielding, has not been fully explored. Summary of the Invention
[0004] The purpose of this invention is to provide a leather-based samarium boride composite material, its preparation method, and its application. By combining a leather matrix with a neutron-absorbing component, a novel neutron protection material with both structural designability and functional controllability is constructed, which is expected to break through the performance bottleneck of traditional materials.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] This invention provides a method for preparing a leather-based samarium boride composite material, comprising the following steps:
[0007] The leather substrate was immersed in a samarium boride solution, and after compounding, it was dehydrated and dried in sequence to obtain a leather-based samarium boride composite material.
[0008] Preferably, the leather base comprises vegetable-tanned or chrome-tanned cowhide.
[0009] Preferably, the concentration of the samarium boride solution is 20–40 wt%.
[0010] Preferably, the impregnation temperature is 20–50°C and the time is 4–10 hours.
[0011] Preferably, the dehydration treatment is carried out at a temperature of 30–50°C for 24–36 hours.
[0012] Preferably, the drying method is vacuum high-temperature drying or vacuum freeze drying.
[0013] Preferably, the vacuum high-temperature drying temperature is 80-100℃ and the time is 2-5 hours; the vacuum freeze-drying temperature is -40--65℃ and the time is 6-24 hours.
[0014] This invention provides a leather-based samarium boride composite material prepared by the preparation method described in the above technical solution.
[0015] This invention provides the application of the leather-based samarium boride composite material described above in the field of neutron protection.
[0016] This invention provides a method for preparing a leather-based samarium boride composite material. Samarium boride is loaded onto natural leather to obtain a novel natural leather composite shielding material. Both Sm and B in samarium boride have large neutron absorption cross sections, which can effectively absorb thermal neutrons, thereby improving neutron shielding efficiency. Simultaneously, this invention utilizes the multi-level supramolecular assembly structure of natural leather, composed of a three-dimensional framework of amino acid-peptide chains-triple helices-microfibrils-fibrils-collagen fibers-fiber bundles-fiber networks. Furthermore, this invention leverages the natural porous structure of leather collagen fibers, combined with impregnation technology, to uniformly load samarium boride into the fiber network, constructing a neutron-absorbing functional phase. This stabilizes and disperses samarium boride in the natural leather, achieving effective bonding between samarium boride and the leather substrate, improving the dispersibility of the samarium boride filler, and obtaining a high-performance neutron protection material based on a leather matrix.
[0017] This invention not only expands the high-value-added application scenarios of leather materials and promotes the green and multifunctional development of nuclear protection materials, but also provides theoretical basis and technical path for the innovative application of biomass resources in the field of radiation protection. It is expected to provide new material solutions for the lightweight design of protective equipment for nuclear power plant workers, shielding layers for mobile nuclear facilities, and medical neutron therapy equipment, while promoting the transformation and upgrading of the leather industry to the high-tech field. Attached Figure Description
[0018] Figure 1 The data represent the percentage of B element content in leather-based samarium boride composite materials prepared under different reaction temperature conditions in Example 1.
[0019] Figure 2 The data per unit volume of B in the leather-based samarium boride composite material prepared in Example 2 are as follows:
[0020] Figure 3 The data on the B element content in the composite materials prepared at different reaction temperatures and reaction times in Example 3;
[0021] Figure 4 This is a comparison chart of the B element content in leather-based samarium boride composite materials prepared by different drying methods in Example 4;
[0022] Figure 5 Data on the B element content in vegetable-tanned bovine hide-based SmB6 materials and chrome-tanned bovine hide-based SmB6 materials prepared at different concentrations in Example 5;
[0023] Figure 6 The data for neutron shielding efficiency of vegetable-tanned bovine hide-based SmB6 materials and chrome-tanned bovine hide-based SmB6 materials prepared at different concentrations in Example 5 are as follows:
[0024] Figure 7 Figure showing the B element content in leather-based samarium boride composites prepared from SmB6 aqueous solutions of different concentrations;
[0025] Figure 8 The tensile strength and elongation data of SmB6 leather-based composites with different B contents are shown, where (a) is the tensile strength and (b) is the elongation.
[0026] Figure 9 The results of air permeability and water permeability tests on SmB6 leather-based composite materials with different B contents are shown, where (a) is the moisture permeability and (b) is the air permeability.
[0027] Figure 10 Neutron shielding efficiency data for leather-based composite materials prepared from SmB6 aqueous solutions of different concentrations. Detailed Implementation
[0028] In this invention, unless otherwise specified, the raw materials or reagents required for preparation are all commercially available products well known to those skilled in the art.
[0029] This invention provides a method for preparing a leather-based samarium boride composite material, comprising the following steps:
[0030] The leather substrate was immersed in a samarium boride solution, and after compounding, it was dehydrated and dried in sequence to obtain a leather-based samarium boride composite material.
[0031] In this invention, the leather base preferably comprises vegetable-tanned or chrome-tanned cowhide. This invention does not impose any specific limitation on the specific source of the leather base; commercially available products well-known in the art are acceptable.
[0032] Before the impregnation, the present invention preferably cuts the leather base sample into a size of 9 mm radius and 1.2 mm thickness, and dehydrates it with anhydrous ethanol for 24 h.
[0033] In this invention, the concentration of the samarium boride solution is preferably 20-40 wt%, more preferably 30-40 wt%, and even more preferably 40 wt%. This invention does not impose any special limitations on the preparation process of the samarium boride solution; a solution of the corresponding concentration can be prepared using water according to methods well known in the art.
[0034] In this invention, the immersion temperature is preferably 20-50°C, more preferably 30-40°C, and the immersion time is preferably 4-10 hours, more preferably 6-8 hours.
[0035] In this invention, the temperature of the dehydration treatment is preferably 30-50°C, more preferably 30-40°C, and the time is preferably 24-36 hours, more preferably 24-28 hours.
[0036] In this invention, the drying method is preferably vacuum high-temperature drying or vacuum freeze-drying, and more preferably vacuum high-temperature drying.
[0037] In this invention, the temperature of the vacuum high-temperature drying is preferably 80-100℃, more preferably 80-90℃, and the time is preferably 2-5h, more preferably 2-4h; the temperature of the vacuum freeze-drying is preferably -40--65℃, more preferably -62℃, and the time is preferably 6-24h, more preferably 8-12h.
[0038] This invention provides a leather-based samarium boride composite material prepared by the preparation method described in the above technical solution.
[0039] This invention provides the application of the leather-based samarium boride composite material described above in the field of neutron protection. This invention does not specifically limit the method of application; any method well-known in the art can be used.
[0040] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.
[0041] Unless otherwise specified, the experimental and testing methods described below are conventional methods; unless otherwise specified, the reagents and raw materials described below are commercially available.
[0042] This invention studies the structure-property relationship between preparation process, microstructure control and neutron shielding performance.
[0043] Example 1
[0044] Chrome-tanned cowhide samples were cut into sizes with a radius of 9 mm and a thickness of 1.2 mm. After dehydration with anhydrous ethanol for 24 h, the resulting cowhide samples were immersed in a 40 wt% SmB6 aqueous solution under atmospheric pressure. Each group of samples was reacted for 6 h at different temperatures (10℃, 20℃, 30℃, 40℃, 50℃) as shown in Table 1. The resulting composite material was dehydrated with anhydrous ethanol at 30℃ for 24 h, and then placed in a vacuum drying oven at 80℃ for 2 h to obtain a leather-based samarium boride composite material.
[0045] Table 1. Experimental conditions for single factors
[0046]
[0047] The percentage data of B element content in leather-based samarium boride composite materials prepared under different reaction temperature conditions in Example 1 are as follows: Figure 1 As shown.
[0048] Example 2
[0049] The only difference from Example 1 is that each group of samples was reacted at 40°C for different times (2h, 4h, 6h, 8h, 10h) according to Table 1.
[0050] Figure 2 The percentage data of element B in the leather-based samarium boride composite material prepared in Example 2.
[0051] Depend on Figures 1-2 It is known that the reaction time and reaction temperature during the synthesis process have a significant impact on the actual content of fillers in the composite material. This invention produces a composite material with a high B element content at a specific reaction temperature and time.
[0052] Example 3
[0053] Following the method of Example 1, impregnation was performed according to the reaction temperature and time in Table 2 to obtain the corresponding composite material.
[0054] Table 2 Reaction conditions in Example 3
[0055]
[0056]
[0057] The results of the B element content in the composite materials prepared at different reaction temperatures and reaction times in Example 3 are shown below. Figure 3 .
[0058] Depend on Figure 3 It can be seen that the composite material prepared at 40℃ for 6 hours has the highest content of element B.
[0059] Example 4
[0060] Chrome-tanned cowhide samples were cut into 9 mm radius and 1.2 mm thickness. After dehydration with anhydrous ethanol for 24 h, the resulting cowhide samples were immersed in a 40 wt% SmB6 aqueous solution at atmospheric pressure and 40 °C for 6 h. The resulting composite material was then dehydrated with anhydrous ethanol at 30 °C for 24 h. After removal, it was dried using different drying methods (vacuum freeze drying at -62 °C for 12 h, air drying at room temperature, high-temperature drying at 100 °C for 2 h, or vacuum high-temperature drying at 80 °C for 2 h) to obtain leather-based samarium boride composite material.
[0061] Figure 4 This is a comparison chart of the B element content in leather-based samarium boride composite materials prepared by different drying methods in Example 4. Figure 4 The results show that, under the same preparation conditions, the sample prepared by vacuum high-temperature drying has a higher content of element B among samples prepared by different drying methods.
[0062] Example 5
[0063] Chrome-tanned and vegetable-tanned cowhide samples were cut into circular samples with a radius of 9 mm and a thickness of 1.2 mm. After dehydration with anhydrous ethanol for 24 h, the resulting cowhide samples were immersed in SmB6 aqueous solutions with concentrations of 20 wt% and 40 wt%, respectively, for 6 h at atmospheric pressure and 40 °C. The resulting composite materials were then dehydrated with anhydrous ethanol at 30 °C for 24 h, removed, and placed in a vacuum drying oven at 80 °C for 2 h to obtain vegetable-tanned cowhide-based SmB6 materials and chrome-tanned cowhide-based SmB6 materials, respectively.
[0064] Figure 5 This section presents data on the B element content in vegetable-tanned bovine hide-based SmB6 materials and chrome-tanned bovine hide-based SmB6 materials prepared at different concentrations in Example 5. Figure 5 It can be seen that, under the same conditions, when samarium hexaboride samples of chrome-tanned leather matrix and vegetable-tanned leather matrix were prepared using solutions of the same concentration, the chrome-tanned leather matrix sample had a higher content of element B.
[0065] Neutron shielding performance was tested at the Thermal Neutron Flux Rate Standard Laboratory of the National Institute of Metrology, China. The thermal neutron shielding performance was tested using a neutron transport experiment. Specifically, the test system included a neutron source, a collimator, and a neutron detector. An americium-beryllium (Am-Be) source with an average energy of 4.5 MeV and a flux rate of 10⁶ n / cm²s was selected as the neutron point source. The internal thermal neutron flux rate was 21410 ± 492 cm². -2 ·s -1External thermal neutron flux rate: 2042±47 cm⁻¹ -2 ·s -1 Heavy water was used as the neutron source moderator. Thermal neutron decay was measured using a neutron detector. A 1 mm thick Pb sheet was selected as the response tuning component for absorbing thermal neutrons. A 10 mm × 10 mm leather sample was placed in an outdoor field, and the sample was tested individually.
[0066] Figure 6 The data presents the neutron shielding efficiency of vegetable-tanned bovine hide-based SmB6 materials and chrome-tanned bovine hide-based SmB6 materials prepared at different concentrations in Example 5. Figure 6 It can be seen that, under the same conditions, when using solutions of equal concentration to prepare samarium hexaboride samples with chrome-tanned and vegetable-tanned leather matrices respectively, the neutron shielding efficiency of the chrome-tanned leather matrix sample is significantly higher than that of the vegetable-tanned leather matrix sample.
[0067] Example 6
[0068] The chrome-tanned cowhide sample was cut into circular samples with a radius of 9 mm and a thickness of 1.2 mm. After dehydration with anhydrous ethanol for 24 h, the resulting cowhide sample was immersed in SmB6 aqueous solutions with concentrations of 0 (pure water), 10, 20, 30, 40, 50 and 60 wt% respectively, and immersed for 6 h at atmospheric pressure and 40 °C. The resulting composite material was dehydrated with anhydrous ethanol at 30 °C for 24 h, and then placed in a vacuum drying oven at 80 °C for 2 h to obtain chrome-tanned cowhide-based SmB6 material.
[0069] Test results of Example 6
[0070] 1) B element content
[0071] Since the material preparation uses an aqueous solution impregnation method, the absorbed filler content is not the same as the added amount. ICP-OES was used to further detect the B element content in the samples, and the samples were named using the B element content. The B element content is shown in Table 3. Figure 7 The leather sample was renamed Bx-NL based on its B element content (x represents the B element content).
[0072] Table 3. B element content in samples prepared from SmB6 aqueous solutions of different concentrations
[0073]
[0074] From Table 3 and Figure 7 It can be seen that the actual content of element B increases with the increase of the concentration of the SmB6 aqueous solution used.
[0075] 2) Tensile strength and tensile elongation
[0076] Tensile strength and elongation were tested on SmB6 leather-based composites with different B contents. The results are shown in [Figure number missing]. Figure 8 , where (a) is tensile strength and (b) is tensile elongation;
[0077] Depend on Figure 8 It can be seen that as the content of SmB6 filler increases, the tensile strength and elongation of the material decrease accordingly. The tensile strength of B14.1-NL is 9.285 MPa and the elongation is 51%.
[0078] 3) Breathability and water permeability
[0079] The air permeability and water permeability of SmB6 leather-based composites with different boron contents were tested, and the effect of boron content on air permeability and water permeability was investigated. The results are shown in [Figure Number]. Figure 9 , where (a) is the moisture permeability and (b) is the air permeability.
[0080] Depend on Figure 9 It can be seen that as the content of element B increases, both air permeability and water permeability decrease to varying degrees, but the content of element B has little effect on water permeability. The moisture permeability of B14.1-NL is still above 4000.
[0081] 4) Neutron shielding rate
[0082] Neutron shielding efficiency tests were conducted on leather-based composite materials prepared with SmB6 solutions of different concentrations. The results are shown in [Figure number missing]. Figure 10 And Table 4.
[0083] Table 4 Neutron shielding efficiency of different samples in Example 6
[0084]
[0085] Depend on Figure 10 As shown in Table 4, the neutron shielding efficiency of the material gradually increases with the increase of SmB6 filler content.
[0086] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a leather-based samarium boride composite material, characterized in that, Includes the following steps: The leather substrate was immersed in a samarium boride solution, and after compounding, it was dehydrated and dried in sequence to obtain a leather-based samarium boride composite material.
2. The preparation method according to claim 1, characterized in that, The leather base includes vegetable-tanned or chrome-tanned cowhide.
3. The preparation method according to claim 1 or 2, characterized in that, The concentration of the samarium boride solution is 20–40 wt%.
4. The preparation method according to claim 3, characterized in that, The immersion temperature is 20–50°C, and the time is 4–10 hours.
5. The preparation method according to claim 1, characterized in that, The dehydration treatment is carried out at a temperature of 30–50°C for 24–36 hours.
6. The preparation method according to claim 1, characterized in that, The drying method is vacuum high-temperature drying or vacuum freeze drying.
7. The preparation method according to claim 6, characterized in that, The vacuum high-temperature drying temperature is 80-100℃ and the time is 2-5 hours; the vacuum freeze-drying temperature is -40--65℃ and the time is 6-24 hours.
8. The leather-based samarium boride composite material prepared by the preparation method according to any one of claims 1 to 7.
9. The application of the leather-based samarium boride composite material of claim 8 in the field of neutron protection.